Do Fundamentals Drive Cryptocurrencies’ Market Value? A Study Of Developer And User Activities In Cryptocurrency Market - Yariza, Muhammad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
In this study, I undertake a comprehensive examination of developer and user activities as determinants in the variations of cryptocurrencies' market values. The metrics for developer activities are sourced from GitHub and include commits, open issues, closed issues, open pull requests, merged pull requests, and releases. For user activities, transaction on-chain metrics are employed, specifically active addresses, transactions, and wallet address. By utilizing these metrics, the study examines the relationship between these activities and both market capitalization and return in the context of cryptocurrencies. This study finds that these metrics explain the variation of the cryptocurrencies’ value in the market.